Influencers and Social Cues on Purchase Intention in the Digital Era : A Sistematic Literature Review - Apriyanto, Dhidik (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
The goal of this study is to explore how influencers use social cues to shape consumer purchase intentions. By reviewing 491 articles, with a focus on 218 full-text studies listed in Scopus, this research examines the effectiveness of social cues in influencer marketing. In today's digital world, influencers and social cues play a major role in influencing what consumers decide to buy. With their credibility, charm, and the interactions they create on social media, influencers can significantly shape how consumers feel about the products or brands they promote. More than just promoting products, influencers create a deeper connection with their followers through social cues, like social engagement, which strengthens the emotional bond. This connection encourages consumers to trust and engage more with the products they recommend. Studies show that an influencer's credibility directly impacts consumers' purchasing decisions. Other factors, like attractiveness and interactivity, also play important roles when the relationship between an influencer and their followers feels more personal, consumers are more likely to buy. So, influencers aren't just mediators between brands and consumers; they also help create more personal experiences that significantly influence purchasing choices. Keyword: influencer, social cues, purchase intention